2019
DOI: 10.1126/science.aay8855
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the movement for mountain peoples and policies

Abstract: Policies can have impacts extending far downstream

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Options: In this context, concepts and models of mountain social-ecological systems (Altaweel et al 2016;Klein et al 2019) and initiatives, such as Mountain Social Ecological Observatory Networks (Alessa et al 2018), the Zones Ateliers Alpes (http://www.za-alpes.org/) or the Trajectories project (https://trajectories.univ-grenoble-alpes.fr/), appear to be useful integration frameworks, both spatially and temporally, as well as in terms of methodologies, disciplines, and stakeholders (Alessa et al 2018;Grêt-Regamey et al 2019). Remark: Similar calls for a landscape perspective to account for the impact of upstream activities on downstream areas have recently been formulated (Makino et al 2019).…”
Section: Recommendation 1: Improving Biodiversity Informationmentioning
confidence: 99%
“…Options: In this context, concepts and models of mountain social-ecological systems (Altaweel et al 2016;Klein et al 2019) and initiatives, such as Mountain Social Ecological Observatory Networks (Alessa et al 2018), the Zones Ateliers Alpes (http://www.za-alpes.org/) or the Trajectories project (https://trajectories.univ-grenoble-alpes.fr/), appear to be useful integration frameworks, both spatially and temporally, as well as in terms of methodologies, disciplines, and stakeholders (Alessa et al 2018;Grêt-Regamey et al 2019). Remark: Similar calls for a landscape perspective to account for the impact of upstream activities on downstream areas have recently been formulated (Makino et al 2019).…”
Section: Recommendation 1: Improving Biodiversity Informationmentioning
confidence: 99%
“…In addition, among the signatory nations of the Mountain Partnership, only one – Andorra – has formally included mountain sustainability as foundational to national development planning (Makino et al . 2019).…”
Section: Figurementioning
confidence: 99%
“…Although the majority of these partnerships rely on a systems approach to collaborative work on mountains, a recent overview of international policies for mountains, while spotlighting important knowledge gaps, reported that there is “little information on how land use in mountains is changing” and that studies are either fragmented or “focused on highly specific locations” (Makino et al . 2019). In fact, due in part to the groups described above, there exists a rich literature portraying multiple aspects of global land use and adaptations to change in mountains.…”
Section: Partnerships For Mountainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern Africa's third-world context necessitates a sensitive and strategic approach to addressing change in its mountain regions. Embracing its social environment through social engagement [133], public-assisted monitoring [32], and the crafting of innovative solutions for mountain futures [134] are key features to consider in future LTSER, given that mountains and their associated ecosystem services are critical for people [24,41,135,136] and are cradles of cultural and ethnic diversity [137,138]. The first pioneering form of mountain LTSER in South Africa took place in the impoverished rural Okhombe and Obonjaneni communities in the upper Tugela catchment of the northern Maloti-Drakensberg [139].…”
Section: Moving Towards Systems-based Landscape-scaled Ltsermentioning
confidence: 99%